2016
DOI: 10.4049/jimmunol.1600095
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Cutting Edge: Role of NK Cells and Surfactant Protein D in Dendritic Cell Lymph Node Homing: Effects of Ozone Exposure

Abstract: 2016. Cutting edge: role of NK cells and surfactant protein D in dendritic cell lymph node homing: effects of ozone exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…A study by Ge et al (48) showed that SP-D binds directly to pulmonary natural killer (NK) cells through the receptor NKp46 and thereby induces secretion of IFN-γ (Figure 3). This is the most specific receptor for NK cells and is expressed on the surface of all NK cell subsets (82, 83).…”
Section: In Vitro Studies Of Sp-d-mediated Cellular Effectsmentioning
confidence: 99%
“…A study by Ge et al (48) showed that SP-D binds directly to pulmonary natural killer (NK) cells through the receptor NKp46 and thereby induces secretion of IFN-γ (Figure 3). This is the most specific receptor for NK cells and is expressed on the surface of all NK cell subsets (82, 83).…”
Section: In Vitro Studies Of Sp-d-mediated Cellular Effectsmentioning
confidence: 99%
“…Natural killer (NK) cells are an essential component of the anti-viral immune response. However, little is known about their interaction with SP-A and SP-D. A study by Ge et al demonstrated a decreased IFN-γ expression in SP-D knockout mice upon ozone exposure ( 69 ). The authors hypothesized that this decrease was as a result of the absence of SP-D interacting with the glycosylated NKp46 receptor on NK cells ( 69 ).…”
Section: Immunomodulatory Functions Of Sp-a and Sp-dmentioning
confidence: 99%
“…However, little is known about their interaction with SP-A and SP-D. A study by Ge et al demonstrated a decreased IFN-γ expression in SP-D knockout mice upon ozone exposure ( 69 ). The authors hypothesized that this decrease was as a result of the absence of SP-D interacting with the glycosylated NKp46 receptor on NK cells ( 69 ). They further postulated that this could play a role in the impaired dendritic cell homing to lymphoid tissue seen in SP-D knockout mice.…”
Section: Immunomodulatory Functions Of Sp-a and Sp-dmentioning
confidence: 99%
“…SP-D воздействует на адаптивную иммунную систему, модулируя апоптоз Т-клеток [24][25][26]. Согласно [27], взаимодействие SP-A и SP-D с дендритными клетками происходит за Более глубокое и детальное изучение роли SP-A и SP-D позволяет предположить, насколько велико их значение для всего организма. За последние годы накоплено большое количество информации о системах внелегочных органов, в которых обнаружены данные белки.…”
Section: рис 1 процедура отбора источников для литературного обзораunclassified